PERAN BRAND AWARENESS DALAM MEMEDIASI PENGARUH DAYA TARIK IKLAN TERHADAP BRAND ATTITUDE - Pandit Praschita, I Wayan; Giantari, I. G. A. Ketut (E-Jurnal Manajemen; Vol 8 No 2 (2019)DO - 10.24843/EJMUNUD.2019.v08.i02.p17, 2019)
ABSTRACT The purpose of this study is to explain the role of brand awareness in mediating the effect of ad attractiveness on brand attitude. The population used is Shampoo Clear consumers in Denpasar City. The sample was determined by purposive sampling method totaling 110 respondents. Data were collected through questionnaires and analyzed using path analysis techniques and double test. The results showed that the attractiveness of advertising and brand awareness each had a positive and significant impact on the brand attitude and the mediating role of brand awareness that increased the relationship between ad attractiveness and brand attitude. Shampoo Clear Men must strengthen the attractiveness used in its advertisements because it will have an impact on consumer awareness of the Clear Men Shampoo brand. High brand awareness will encourage positive consumer attitudes towards the Clear Men Shampoo brand. Keywords: ad attractiveness, brand awareness, brand attitude